Representation of Elephants in Vijayanagara Art – Relevance, Symbolism and Interpretations - Thakur, P. (Centre for Asian Studies, University of Kelaniya, Sri Lanka, 2016)
The paper is an attempt to discuss the depiction of Asian elephants as a dominant element throughout the sculptural art of the 14th – 15th century South India with special reference to the Vijayanagara Empire. Elephant have always been a prominent motif in both civil and religious art and architecture in India. In the sculptural reliefs found on the various monuments spread throughout extent of the Vijayanagara Empire, man’s ascendancy over the animals has been well depicted and captured. The representations are varied in themes and include scenes of capturing of calf from the forest, taming of the young ones, training in war fare as well as load bearer. The scenes also provide the glimpse of use of elephants in hunting by the royalty. The majority of the portrayal shows the grand beast in military procession in company of soldiers and under animals like horses and camels. Some sculptures show ropes running across their legs thus suggesting their tameness. The animal is represented in various forms of medium – as carved in high reliefs on running series of consecutive panels, balustrades, pillars, load bearing architectural motifs or independent sculptures.
Keywords: Motif; Sculptural Reliefs; Karnataka; South India; Vijayanagara